Studi Komparatif Komunikasi Interpersonal Pegawai Berdasarkan Jenis kelamin Pada Satuan Polisi Pamong Praja Kota Padang - Indah Saputri; Ermita .; Lusi Susanti; Tia Ayu Ningrum (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This study is motivated by the importance of interpersonal communication in supporting the smooth implementation of tasks and creating harmonious working relationships within the Satuan Polisi Pamong Praja (Satpol PP) of Padang City. The problem addressed is whether there is a difference in employees' interpersonal communication based on gender. This study aims to determine the difference in employees' interpersonal communication based on gender at Satpol PP Kota Padang. This is a quantitative comparative study with a population of 469 employees and a sample of 217 employees determined using the Proportionate Stratified Random Sampling technique. The research instrument was a Likert-scale questionnaire that had been tested for validity and reliability. Data were analyzed using descriptive statistics (mean) and inferential statistics using the Mann-Whitney U Test with the assistance of SPSS version 26.0. The results show that employees' interpersonal communication falls into the effective category, with average scores of 4.20 for openness, 4.08 for supportiveness, 4.06 for equality, 3.97 for empathy, and 4.18 for positiveness. The Mann-Whitney U Test result shows an Asymp. Sig. (2-tailed) value of 0.474 (> 0.05), indicating that there is no significant difference in interpersonal communication between male and female employees at Satpol PP Kota Padang.